Optimizing bitter gourd (Momordica charantia) production through carrageenan-fertilizer synergy - AL-BASSER BANO ANAYATIN; MYRNA GEMENTIZA PABIONA; JUNESA UDTOJAN CRISTOBAL; ROMIL TAN; JOHN REY NATINGA LABAJO (Nusantara Bioscience, 2025)
Abstract. Anayatin AB, Pabiona MG, Cristobal JU, Tan R, Labajo JRN. 2025. Optimizing bitter gourd (Momordica charantia) production through carrageenan-fertilizer synergy. Nusantara Bioscience 17: 169-177. This study evaluates the synergistic effects of combining radiation-modified Carrageenan Plant Growth Promoter (PGP) with the Recommended Rate of Inorganic Fertilizer (RRIF) on the growth, nutrient dynamics, and yield of Momordica charantia L. (bitter gourd or ampalaya). Through a Randomized Complete Block Design (RCBD) replicated three times, treatments integrating RRIF and Carrageenan PGP were tested for their impact on plant height, soil properties, nutrient content, and fruit morphology. Results revealed that *Full RRIF + 4.5L ha?¹ Carrageenan PGP* significantly enhanced fruit yield (64.50 tons ha?¹) and achieved the highest return on investment (ROI: 435.30%), underscoring its economic viability. Meanwhile, ½ RRIF + 9L ha?¹ Carrageenan PGP produced the largest fruit diameter (49.44 mm) and highest total nitrogen (2.60%) and crude protein (16.24%) content, highlighting its role in improving nutritional quality. Mid-growth plant height (29 DAT) exhibited strong correlations with fruit weight (r = 0.475), length (r = 0.482), and diameter (r = 0.647), emphasizing the critical role of vegetative vigor in later stages for optimizing fruit development. Notably, earlier flowering (26 DAT under Full RRIF) correlated negatively with fruit weight (r = -0.558) and length (r = -0.532), suggesting accelerated reproductive phases enhance resource allocation to fruit traits. Carrageenan PGP applications stabilized soil moisture (92.30-93.82%) and maintained adequate phosphorus/potassium levels while significantly boosting soil organic matter (1.48%) and nitrogen content (0.074%) in Full RRIF treatments. The stability of these soil parameters, coupled with enhanced nutrient partitioning efficiency, positions Carrageenan PGP as a sustainable alternative to conventional fertilization. This study advocates for integrating Carrageenan PGP with reduced inorganic fertilizers to balance productivity, soil health, and economic returns. Future research should explore long-term impacts on soil microbial diversity, carbon sequestration, and scalability across diverse agroecological zones to refine protocols for sustainable M. charantia cultivation.